Buckling instability of viral capsides - Aland, Sebastian; Rätz, Andreas; Röger, Matthias; Voigt, Axel (Technische Universität Dortmund, 2011)
The crystallographic structure of spherical viruses is modeled using a multiscale approach combining a macroscopic Helfrich model for morphology evolution with a microscopic approximation of a classical density functional theory for the protein interactions. The derivation of the model is based on energy dissipation and conservation of protein number density. The resulting set of equations is solved within a diffuse domain approach using finite elements and shows buckling transitions of spherical into faceted viral shapes.
a continuum approach
Keywords: 610